Amar a deus e amar a si: imagens no espelho da experiência mística em marguerite porete - Pontes, Amanda Oliveira da Silva (2016)
Marguerite Porete is a French mystic of the thirteenth century which showed particular interest in defending what is most intimate in the human, what he has in his heart is the seal of eternity and this stamp printed in the soul is Love. The speech of this woman is focused mainly on point the divine and eternal nature of the soul (love) and how this soul perceives and returns to its essence from his mystical encounter with God. In this dissertation, organize the principles that guide the union of experience and return this soul to the Divinity, in order to discuss the idea of the soul as love God and becomes God itself is love, as it is the mirror and image God's. As a result of analysis of the concepts of soul, love and otherness investigated in the book of Marguerite Porete (The mirror of simple and annihilated souls and only remain in the will and desire of love) we come to reflect on how the soul discovers and resurfaces in form of God and united to the Trinity through the presence of Love. In poretiana work, this idea is shown translated in the metaphor of God's image in the mirror of the soul.